2012
DOI: 10.1098/rsbl.2012.0460
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for an Asian origin of monitor lizards followed by Tertiary dispersals to Africa and Australasia

Abstract: Monitor lizards are emblematic reptiles that are widely distributed in the Old World. Although relatively well studied in vertebrate research, their biogeographic history is still controversial. We constructed a molecular dataset for 54 anguimorph species, including representatives of all families with detailed sampling of the Varanidae (38 species). Our results are consistent with an Asian origin of the Varanidae followed by a dispersal to Africa 41 (49–33) Ma, possibly via an Iranian route. Another major eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 23 publications
6
68
0
Order By: Relevance
“…The subgenus is geographically restricted to a large region east of Wallace’s line with the Solomon Islands and parts of Micronesia forming the eastern and northern boundaries (Ziegler et al 2007a, Sweet and Pianka 2007). The systematic arrangement is well-supported by molecular and morphological studies (Ziegler and Böhme 1997, Fitch et al 2006, Vidal et al 2012). Several new monitor lizards of the subgenus Euprepiosaurus have been discovered from islands in the southwest Pacific since the early 1990s.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The subgenus is geographically restricted to a large region east of Wallace’s line with the Solomon Islands and parts of Micronesia forming the eastern and northern boundaries (Ziegler et al 2007a, Sweet and Pianka 2007). The systematic arrangement is well-supported by molecular and morphological studies (Ziegler and Böhme 1997, Fitch et al 2006, Vidal et al 2012). Several new monitor lizards of the subgenus Euprepiosaurus have been discovered from islands in the southwest Pacific since the early 1990s.…”
Section: Introductionsupporting
confidence: 62%
“…Varanus semotus is notable as it is separated from its closest relatives by hundreds of kilometers of open sea and must have colonized the oceanic Mussau Island through long distance oversea dispersal, most likely by rafting. Vidal et al (2012) estimate the age of Varanus indicus species group at around 6–11.5 mya. With this time reference the subsequent lineage diversification of species group should have occurred sometime in the late Miocene to early Pleistocene during which it is also likely that Mussau was colonized.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the earliest evidence of the genus on the European continent is recorded in the early Miocene of Spain (Delfino et al, 2013). Whether these early Miocene immigrants originated directly from Africa (Holmes et al, 2010) or have Asian affinities (Conrad et al, 2012;Vidal et al, 2012;Rage, 2013) cannot be demonstrated with certainty. The occurrence of Varanus-like forms in the late Eocene and early Oligocene of Egypt (Smith et al, 2008;Holmes et al, 2010) favors an African origin, but the Asian record is too poor to offer any insights.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genetic phylogenies of Varanidae exist (Ast, 2001; Clemente et al., 2009; Fitch, Goodman, & Donnellan, 2006; Vidal et al., 2012), and the consensus is that four major clades are present in Australia; the pygmy monitors (“Odatria” clade), the sand monitors (“Gouldii” clade), the lace monitors (“Varius” clade), and the mangrove monitors (“Indicus” clade). Odatria may be further divided into the “Tristis” and “Acanthurus” clades (Table 1).…”
Section: Methodsmentioning
confidence: 99%